Acute Respiratory Distress Syndrome: Respiratory Monitoring and Pulmonary Physiology - Coudroy, Remi; Chen, Lu; Pham, Tài; Piraino, Thomas; Telias, Irene; Brochard, Laurent (Seminars in Respiratory and Critical Care Medicine, 2019)
The high prevalence of acute respiratory distress syndrome (ARDS), its morbidity and mortality continue to fare a huge burden in the intensive care unit. More than 40 years ago, experimental studies have highlighted that, albeit essential, mechanical ventilation could be harmful to lungs and more recently to the diaphragm. Despite life-saving advances in mechanical ventilation (such as low tidal-volume ventilation, neuromuscular blockers agents, or prone positioning), a recent international observational study reported that most ARDS patients were not appropriately monitored. The monitoring capabilities of ventilators, in particular the simple interaction of the patient and the mechanical ventilation, are very powerful but are underutilized. This lack of monitoring may contribute to the persisting poor outcome of patients with ARDS. Providing a more careful ventilation is a priority to improve patients' outcomes. To achieve this goal, it is of paramount importance to better understand the complex relationship between the patient and the ventilator: the impact of ventilator settings on lungs during passive controlled ventilation, but also of patient's breathing efforts on lungs during assisted ventilation. In this review we present available tools to monitor respiratory mechanics at the bedside aiming at optimizing and personalizing mechanical ventilation. Hopefully, this careful management can decrease mortality of patients with ARDS in the future.
Keywords: acute respiratory distress syndrome; mechanical ventilation; respiratory physiology